Simple methods for fluidic drag estimation during pipe installation via HDD. (June 2018) - Rabiei, Montazar; Yi, Yaolin; Bayat, Alireza; Cheng, Roger
Highlights: A set of practical methods for determining fluid drag during HDD pullback is proposed The methods account for drilling fluid rheology and pullback velocity. The methods estimations differ slightly from Finite Volume Method results. Abstract: This paper proposes a series of simple methods for fluidic drag evaluation of non-Newtonian slurries flowing within a bore during Horizontal Directional Drilling (HDD) pipe installation operations. The methods are based on adapting the solutions of annular and planar Couette flow problems to the HDD pullback problem and are favorable for practical uses by the HDD industry. In comparison to the existing methods, the proposed method accounts for a wide range of parameters, including slurry rheology, bore geometry, and pullback rate. For verification purposes, verified fluidic drag forces for two actual HDD crossings have been used. Comparison of the forces obtained via different methods confirms the ability of the new simple methods to capture the fluidic drag changes accurately.